(untitled) (LIS TODAY, 2021)
Recent development in information and communication technology especially the internet has brought out significant change in the reading habits of reader in accordance with the way which generate storage repackage and make use of information. The purpose of the study was to focus on reading habits of research scholars in digital/internet environment. A survey of 130 research scholars of BRA Bihar University, Muzaffarpur (Bihar) was done to find reading habits, impact of internet on reading, average time spent on reading, types of reading materials preferred, etc.